Importance of metapopulation dynamics to explain fish persistence in a river system - Bellard, Céline; Hugueny, Bernard (Freshwater biology, 2020)
Habitat modification and fragmentation are key factors responsible for fish population decline worldwide. Previous assessments documented a total of 72 species extinctions for the sole class of Actinopterygii. However, global extinctions are difficult to monitor or study based on fossil records. By contrast, local extinctions occurring at the population level are easier to study. Given this context, an important question relates to whether extinction dynamics studied at the local scale can provide useful information to understand extinctions occurring at larger scales. This would be the case if local extinctions were not balanced by recolonisation as in a classic metapopulation. Our aim is thus to explain the observed regional (per basin) persistence of 252 fish populations by testing contribution of local extinction rates and more generally metapopulation dynamics components. To address this aim, we used the annual extinction probability of 252 regional populations of up to 14 species inhabiting 18 coastal rivers, which became isolated c. 8,500 years ago. We specifically compared extinction probabilities obtained by seven theoretical models to investigate whether regional extinction rates (i.e. loss from a river system) were correlated to local extinction rates (i.e. loss from an occupied site) and the role of metapopulation dynamics to explain regional persistence. Using empirical data, we showed the importance of variables related to metapopulation dynamics to explain extinction rates across the 18 river systems. As expected, the regional extinction rate decreased with the colonisation rate, area, metapopulation size, and percentage of occupied localities. By contrast, an inconsistent relationship emerged between regional and local extinction rates, as species with high local extinction rates were not particularly prone to regional extinction. Our results provide strong support for the contribution of colonisation rates to explain persistence. Overall, our results show that the equilibrium number of occupied localities could be a good predictor of the long‐term persistence of metapopulations in rivers. Finally, our results suggest the importance of connectivity to maintain sustainable populations within the river system.